Effects of the cryolipolysis using the advanced redux method in the treatment of localized adiposity - Soares, Roseane Débora Barbosa; Silva, Rodrigo Marcel Valentim da; Silva, Júlio Costa e; Pinto, Bruna Figueiredo; Farias, Stephan Queiroga; Farias, Ana Lívia Eufrázio de Medeiros; Carreiro, Eneida de Morais; Queiroz, Claudete Arruda Maciel de; Meyer, Patrícia Froes (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Among the techniques used in clinical practice to reduce localized adiposity, cryolipolysis has been highlighted, which is a non-invasive method capable of reducing the thickness of the adipose tissue without damage to the surrounding tissues. However, several associations of techniques suggest an intensification of the results, associating cryolipolysis with other treatments, and the most common is ultracavitation (UCV) or radiofrequency (RF) and massage. Objective: To investigate the effects of cryolipolysis associated with UCV and RF on localized adiposity. Methods: This is a blinded and controlled clinical trial. The sample was composed of 30 females divided into 2 groups of 15: one group received cryolipolysis application in the abdominal region, and performed 1 session of drainage weekly; while another group performed the cryolipolysis and then 8 applications of UCV associated with RF and modeling massage (protocol named Advanced Redux Method – ARM), once a week. The parameters used in cryolipolysis were: temperature: -7ºC; suction pressure: 30 kpa; and application time: 50 min. For the UCV, the parameters were time of 8 minutes, 30w of potency and intensity of 10 w/cm2 . After cryolipolysis, a follow-up of 2 months was performed to verify the changes related to weight, perimeter and thickness of the adipose tissue, measured by ultrasonography. The reassessments were performed 30 and 60 days after the cryolipolysis. Results: It was observed that the ARM promoted a greater reduction of adiposity located in the abdominal region, in the plicometry, perimetry and ultrasonography variables (p<0.05). In the analysis of the questionnaires the ARM group showed lower edema, pain, ecchymosis after application when compared to the group associated only with the drainage. The percentage of satisfaction was also higher in the ARM group. Conclusion: Therefore, it can be observed that the association of UCV, RF and modeling massage through the ARM promoted a higher reduction in adiposity than the group that exclusively performed the cryolipolysis treatment with lymphatic drainage.